Staff Training: A Mandatory Requirement - Mishra, Surendra (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The upward mobility of an organization positively changes its position, responsibilities and financial interests. It is clear that there is an increase in promotion opportunities in the bank due to unionism and the expansion of the bank. Before organizing unions among employees, I felt that the path of promotion was relatively small and I was promoted by employees. Because the employer recognized the merit of the employee instead of the actual merit. However, after the establishment of the union between the employees, the members of the union consider the senior as the main criterion for the promotion. In the case of People with the same seniority were considered criteria of merit. Keywords: Employee training program, Wages, salary and financial incentives